Lipid-mediated signals that regulate mitochondrial biology - Nielson, Jason R.; Rutter, Jared P. (The Journal of biological chemistry, 2018)
For decades, lipids were assumed to fulfill roles only in energy storage and membrane structure. Recent studies have discovered critical roles for phospholipids, sphingolipids, and sterols in many cellular pathways, including cell signaling and transcriptional regulation. Frequently, lipids from these various classes work together to achieve defined cellular outcomes. Specific mitochondrial lipids are critical for proper assembly of the electron transport chain complexes and for effective responses to mitochondrial damage, including maintenance of mitochondrial protein homeostasis, regulation of mitophagy, and induction of apoptosis. In this Minireview, we will primarily focus on mitochondrial lipid signaling mediated by lipid–protein interactions.